2004
DOI: 10.1056/nejmoa042760
|View full text |Cite
|
Sign up to set email alerts
|

Pegaptanib for Neovascular Age-Related Macular Degeneration

Abstract: Pegaptanib for neovascular age-related macular degenerationGragoudas, E.S.; Adamis, A.P.; Cunningham, E.T.; Feinsod, M.; Guyer, D.R.; Study group members AMC, :; Schlingemann, R.O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
908
0
33

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,095 publications
(963 citation statements)
references
References 23 publications
6
908
0
33
Order By: Relevance
“…Bevacizumab, which is approved for the treatment of colon cancer but not for the treatment of AMD, is closely related to ranibizumab. In contrast to pegaptanib that binds only the VEGF isoforms that are 165 kD (VEGF165) and larger [26], both ranibizumab and bevacizumab bind and inhibit all biologically active forms of VEGF [47]. Bevacizumab is a fulllength, humanized monoclonal antibody against VEGF, whereas ranibizumab is a humanized antigen binding fragment against VEGF, and both proteins were genetically engineered from the same murine monoclonal antibody against VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab, which is approved for the treatment of colon cancer but not for the treatment of AMD, is closely related to ranibizumab. In contrast to pegaptanib that binds only the VEGF isoforms that are 165 kD (VEGF165) and larger [26], both ranibizumab and bevacizumab bind and inhibit all biologically active forms of VEGF [47]. Bevacizumab is a fulllength, humanized monoclonal antibody against VEGF, whereas ranibizumab is a humanized antigen binding fragment against VEGF, and both proteins were genetically engineered from the same murine monoclonal antibody against VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…This aptamer binds to VEGF 165 with extremely high affinity (K d ϭ 50 pM), and animal studies and clinical data have demonstrated the efficacy of the aptamer in preventing blood vessel growth and arresting the progression of wet AMD (8,(11)(12)(13)(14). However, the detailed molecular mechanism by which this aptamer achieves isoform-specific inhibition of VEGF 165 is not well understood.…”
mentioning
confidence: 99%
“…[26][27][28][29] For the last decade, anti-VEGF reagents have been developed and approved for clinical use against these neovascular ocular diseases. [30][31][32] Now, the role of VEGF in the progress of retinal diseases is widely recognized in the ophthalmological field. [33][34][35] Surprisingly, we found that Vegf gene deletion induced in retinal pigment epithelium (RPE) cells in the adult mature retina in mice rapidly led to degeneration of the choriocapillaris and the cone photoreceptors, whereas Hif-1α and/or Hif-2α knockout mice exhibited no such phenotype 34 (Fig.…”
Section: Hypoxia Response In Retinal Pathophysiologymentioning
confidence: 99%